Blood metabolites profile and Growth Hormone mRNA expression of Peranakan Ongole cattle fed with finishing ration containing Vinasse-molasses - Fassah, Dilla Mareistia; Nuraini, Nanda Nadhifa; Khotijah, Lilis; Komalasari, Kokom; Suharti, Sri; Astuti, Dewi Apri; Wiryawan, I Komang Gede; Sudarman, Asep; Diapari, Didid (Livestock and Animal Research, 2023)
Objective: This study aimed to investigate effects of Molasses replacement with Vinasse-molasses in ration on the blood metabolite profiles and mRNA expression of Growth Hormone 1 (GH1) of finishing Peranakan Ongole (PO) Cattle.Methods: Ten male PO cattle in averaged 209 ± 21 kg of body weight were equally allocated to receive either molasses or Vinasse-molasses dietary treatments. The concentrate diet was contained of either 15% of molasses (control) or Vinasse-molasses. This study observed the nutrient intake, percentage of weight gain, blood metabolite profiles and GH1 mRNA expression of PO cattle.Results: The result showed that replacing molasses with vinasse-molasses reduced (P<0.05) dry matter intake (DMI) and intakes of crude protein (CP), ether extract (EE), crude fiber (CF), and total digestible nutrient (TDN). Nevertheless, Vinasse-molasses inclusion did not change (P>0.05) percentage of weight gain. Vinasse-molasses increased (P<0.05) the blood urea nitrogen level, while it did not affect (P>0.05) the GH1 mRNA levels.Conclusions: It can be concluded that replacing molasses with vinasse-molasses does not change blood metabolite profile, GH1 mRNA expression and performance of PO cattle.  Vinasse-molasses could be applied as energy sources ingredient to replace molasses in finishing cattle feed.